Self-reported health among migrants. Does contextual discrimination matter? - Philippe Wanner; Marco Pecoraro (Elsevier, 2023)
Background: Switzerland is characterised by significant flows of migrants from different countries of origin and with different levels of education. More than half of recent migrants have reported experiencing prejudice or discriminatory practices in the last 24 months. Methods: Based on a 2018 survey of 7,740 adult migrants (aged 24-64) who arrived in Switzerland in 2006 or later, we examine whether self-reported health is statistically associated with the perception of being a victim of prejudice or discrimination. Ordered logistic regressions are estimated using two indicators of discrimination: the frequency of discrimination and the number of places where discrimination occurs. Results: The regression results show that discrimination, which is not necessarily based on ethnicity or migrant status, is associated with health status, even after controlling for possible confounding factors. Discussion: Our results confirm those already observed in other countries of immigration. They suggest a likely association between perceived discrimination and self-reported health.